2009
DOI: 10.1103/physrevlett.102.099701
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Near-Edge X-Ray Absorption Fine-Structure Investigation of Graphene”

Abstract: A Comment on the Letter by D. Pacilé et al., Phys. Rev. Lett. 101, 066806 (2008)10.1103/PhysRevLett.101.066806. The authors of the Letter offer a Reply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…Figure 4a also suggests that the putative 'interlayer state' ascribed by Pacilé et al, as the intermediate between the π*and the σ*bands, is not an intrinsic feature of SLG [17][18][19] . To arrive at a better understanding of the origin of these features, we have annealed graphene samples in situ.…”
Section: Stxm Mapping Of the Electronic Structure Of Graphenementioning
confidence: 74%
See 2 more Smart Citations
“…Figure 4a also suggests that the putative 'interlayer state' ascribed by Pacilé et al, as the intermediate between the π*and the σ*bands, is not an intrinsic feature of SLG [17][18][19] . To arrive at a better understanding of the origin of these features, we have annealed graphene samples in situ.…”
Section: Stxm Mapping Of the Electronic Structure Of Graphenementioning
confidence: 74%
“…This is contrary to the more common application of the XCH approximation to bound excitons in the X-ray excitations of molecules and molecular condensed phases 14,22,23 . The assignment of the area denoted as interlayer states and the distinctive pre-edge features noted for some of the domains in Figures 1c and 2b have been the topic of much recent contention for single-layered graphene (SLG) [16][17][18][19] . The latter resonance has been ascribed to a peculiarity in the band structure of singlelayered graphene.…”
Section: Stxm Mapping Of the Electronic Structure Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…The origin of peak K has been contentious, and alternative descriptions ascribe it to residual functionalization [39,40], especially the bonding between carbon and oxygen, or a free-electron-like interlayer-state [25,41]. In our SCF-FP result of XANES of the graphene cluster of radius 30Å, for out-of-plane polarization (α=74 • , Fig.…”
Section: Xanes Of Graphenementioning
confidence: 99%
“…One of these studies identified spectral features reflecting the properties of the unoccupied states of a single layer [63]. A splitting of the π * resonance in FLG was ascribed to interlayer states, but these results were later questioned [64]. Recently, the dark-field (df) PEEM method has been demonstrated, [23,65] paving the way to laterally-resolved measurements of the local density of states of the π band.…”
Section: Graphenementioning
confidence: 97%